The Oral Microbiome in Pediatric IBD: A Source of Pathobionts or Biomarkers? - Elmaghrawy, Khalid; Hussey, Séamus; Moran, Gary P. (Frontiers in Pediatrics, 2021)
The oral cavity is continuous with the gastrointestinal tract and in children, oral health may be closely linked with the overall health of the GI tract. In the case of paediatric Crohn’s disease (CD), oral manifestations are an important clinical indicator of intestinal disease. Recent studies of the microbiome in IBD suggest that translocation of oral microbes to the gut may be a common feature of the microbial dysbiosis which is a signature of both CD and ulcerative colitis (UC). Murine studies suggest that translocation of oral bacteria and yeasts to the lower GI tract may trigger inflammation in susceptible hosts, providing a mechanistic link to the development of IBD. Conversely, some studies have shown that dysbiosis of the oral microbiome may occur, possibly as a result of inflammatory responses and could represent a useful source of biomarkers of GI health. This review summarises our current knowledge of the oral microbiome in IBD and presents current hypotheses on the potential role of this community in the pathogenesis of these diseases.